2017
DOI: 10.1111/ijfs.13648
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal resistance and physicochemical attributes of apricots coated with potassium sorbate‐added carboxymethyl cellulose‐based emulsion

Abstract: Summary Antifungal effectiveness of potassium sorbate (KS) incorporated into edible coating composed of carboxymethyl cellulose and candelilla wax blend (CMC‐CnW) was tested on apricots inoculated with fungi. The efficiency of KS‐added coating was higher than KS‐free formulation. The antifungal action of KS‐free coating was likely associated with a reduced access of oxygen to the infection sites and, consequently, modification of the gaseous atmosphere within the fruit tissues. Rhizopus nigricans as the fastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
3
14
3
Order By: Relevance
“…The inhibitory effect of elevated CO 2 level on fungal growth is a well‐known phenomenon (Hocking, ). In contrast to earlier findings (Kowalczyk et al, , ) we found that coating of Brussels sprouts decreased the release of CO 2 (Table ). As a result, the internal atmosphere of the coated vegetables did not offer any antifungal action.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The inhibitory effect of elevated CO 2 level on fungal growth is a well‐known phenomenon (Hocking, ). In contrast to earlier findings (Kowalczyk et al, , ) we found that coating of Brussels sprouts decreased the release of CO 2 (Table ). As a result, the internal atmosphere of the coated vegetables did not offer any antifungal action.…”
Section: Resultscontrasting
confidence: 99%
“…As a consequence of the reduced gas exchange (Table ) and following accumulation of undesired volatiles, an objectionable odor of coated vegetables was detected (Table ). A similar effect has been observed previously for CMC‐CnW‐coated pears and apricots (Kowalczyk et al, , ). The coating provided glossy appearance to Brussels sprouts (Table ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations